Mitochondrial Reactive Oxygen Species Mediate Activation of TRPV1 and Calcium Entry Following Peripheral Sensory Axotomy - Kievit, Bradley; Johnstone, Aaron D.; Gibon, Julien; Barker, Philip A. (Frontiers in Molecular Neuroscience, 2022)
Axons that are physically separated from their soma activate a series of signaling events that results in axonal self-destruction. A critical element of this signaling pathway is an intra-axonal calcium rise that occurs just prior to axonal fragmentation. Previous studies have shown that preventing this calcium rise delays the onset of axon fragmentation, yet the ion channels responsible for the influx, and the mechanisms by which they are activated, are largely unknown. Axonal injury can be modeled in vitro by transecting murine dorsal root ganglia (DRG) sensory axons. We coupled transections with intra-axonal calcium imaging and found that Ca2+ influx is sharply reduced in axons lacking trpv1 (for transient receptor potential cation channel vanilloid 1) and in axons treated with capsazepine (CPZ), a TRPV1 antagonist. Sensory neurons from trpv1–/– mice were partially rescued from degeneration after transection, indicating that TRPV1 normally plays a pro-degenerative role after axonal injury. TRPV1 activity can be regulated by direct post-translational modification induced by reactive oxygen species (ROS). Here, we tested the hypothesis that mitochondrial ROS production induced by axotomy is required for TRPV1 activity and subsequent axonal degeneration. We found that reducing mitochondrial depolarization with NAD+ supplementation or scavenging ROS using NAC or MitoQ sharply attenuates TRPV1-dependent calcium influx induced by axotomy. This study shows that ROS-dependent TRPV1 activation is required for Ca2+ entry after axotomy.